Decontaminating Memory: Governmentality, Networks and Relational Enactment Through Policy Development at the Badger Army Ammunitions Plant, Wisconsin - Norman, Marigold (My University, 2011)
In 1997, the US Army announced that the Badger Army Ammunition Plant (BAAP) in Sauk County, Wisconsin would be decommissioned, marking the end of the site?s complicated history and sparking extensive debate over proposed land uses. The future of the site is still being considered fourteen years on, but some consensus has now been reached on the types of activities considered appropriate for a site with a history so ?deep and ongoing?. Accepted activities for the site, and the more complex and contentious question of land ownership, reflects a cautious intertwining of memory and landscape which has crystallized materially in the landscape.
Includes Bibliography.
Keywords: Badger Army Ammunition Plant; BAAP